Pengaruh Pendekatan Heutagogi Terhadap Kompetensi Siswa Kelas IX pada Pembelajaran Aqidah Akhlak di SMP Muhammadiyah 2 Purwokerto - Firdaus Nur Aflah; Darodjat Darodjat (UM Purwokerto Press, 2023)
The heutagogy approach is one of the approaches used in learning. In this approach, the teacher is a facilitator of students. where the task of the teacher is not only to provide knowledge, but the teacher has a role that is more than that, the teacher has a role as a lifelong teacher, leads the teaching and learning process, directs students in choosing learning resources, and opens communication in learning. With the rapid development of technology, this heutagogi approach is very possible in learning moral aqidah. So that students can easily search for knowledge instantly through the internet. The purpose of this study is to determine the influence of the heutagogi approach in interactive learning on moral aqidah lessons at SMP Muhammadiyah 2 Purwokerto. This research is a type of quantitative research with data collection methods in the form of interviews, questionnaires, and documentation. In this study, researchers used the pearson product moment correlation formula. The results of the research on the heutagogi approach to student competence in learning moral aqidah, related to the heutagogi approach, found a relationship in the very weak category, which obtained a calculated r value of 0.171 or 2.92%, so that the heutagogi approach only gave 2.92% influence on the competence of grade IX students of SMP Muhammadiyah 2 Purwokerto, and the rest of 97.08% came from other factors.